2019
DOI: 10.1136/jech-2018-211985
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in cognitive function of older US adults associated with population changes in demographic and cardiovascular profiles

Abstract: BackgroundRecent estimates suggest that dementia incidence is decreasing in the US possibly due to better management of cardiovascular disease (CVD) risk factors, but these studies lack repeated cross-sectional assessment among a representative US sample. Our objective was to assess temporal trends in cognitive performance in relation to CVD risk factors among older National Health and Nutrition Examination Survey (NHANES) participants.MethodsWe used repeated cross-sectional assessment of 5711 participants ≥60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Reductions in dementia incidence over time may be because of a combination of factors. In the general population, decreasing dementia incidence has been hypothesized to be due in part to improved prevention and management of cardiovascular risk factors for dementia as well as population-level improvements in educational attainment [14,15,31]. Our observation that reductions in incident dementia were more pronounced among PWH may indicate better chronic disease management and attention to modifiable risk factors such as smoking cessation and hypertension control in this population [32,33], which typically has more frequent contact with the healthcare system than the average adult.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in dementia incidence over time may be because of a combination of factors. In the general population, decreasing dementia incidence has been hypothesized to be due in part to improved prevention and management of cardiovascular risk factors for dementia as well as population-level improvements in educational attainment [14,15,31]. Our observation that reductions in incident dementia were more pronounced among PWH may indicate better chronic disease management and attention to modifiable risk factors such as smoking cessation and hypertension control in this population [32,33], which typically has more frequent contact with the healthcare system than the average adult.…”
Section: Discussionmentioning
confidence: 99%
“…Potential explanations are differences of educational systems. Earlier studies have demonstrated that the level of school education has long-lasting effects until old age [9,[37][38][39]. After having acknowledged the pivotal role of school systems, this should lead to efforts to ensure that all segments of the population are profiting while access to a high level of education should not be taken for granted [40,41].…”
Section: Plos Onementioning
confidence: 99%
“…Studies have consistently reported improvements of measured intelligence and cognitive abilities from one generation to the following one. This development became known as the "Flynn-effect" that was described in particular for Germany, France, Israel, Japan, Kenia and the Netherlands, while smaller increases were reported for Brazil, Ireland, New Zealand, Great Britain, and the USA [5][6][7][8][9]. In populations with comparably low levels of cognitive abilities, increases were particularly high, while for Norway and Sweden, stagnation at a very high level was reported.…”
Section: Introductionmentioning
confidence: 99%
“…40 Interestingly, these declines in dementia incidence coincide with improvements in education but also with advances in cardiovascular treatment including medications, public awareness, and stricter treatment guidelines. 41–43 Cumulatively, these data provide compelling evidence to support clinical trials of vascular risk factor treatment to prevent or delay cognitive decline and dementia.…”
mentioning
confidence: 93%